Temperature Coefficient and Q10 Value Estimation for the Growth of Molybdenum-reducing Serratia sp. strain HMY1 (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2018)
A relative 10 ËšC increase in the surrounding temperature, usually results in doubling the reaction rate, with corresponding Q10 value of 2, which is true for a number of biological reactions. Molybdenum reduction to molybdenum blue by bacteria is one of the methods to combat the toxicity of soluble molybdenum to the bacteria. The Q10 values for molybdenum bioreduction, which can be determined from the Arrhenius plots has not previously been reported. A logarithmic plot of growth rate or reduction rates for Serratia sp. strain HMY1 against 1000/temperature (Kelvin) and the slope of the Arrhenius curve was used to obtain the Q10 value in this study. The Q10 value of 2.038 and a theta value of 1.08 obtained in this work, are within the normal range for many biological values.
Keywords: Arrhenius plot, Q10 value, Theta value, molybdenum-reducing bacterium, Serratia sp.